The direct economic impact of the Flint, Michigan, farmers' market relocation. Issue 2 (15th March 2018) - Morckel, Victoria
Abstract: This study considers the effects of location on farmers' market success using the relocation of the farmers' market in Flint, Michigan, as a case study. It examines whether relocating the market benefitted vendors; whether the direct economic impact (DEI) of the market increased post-relocation; whether spending patterns vary by day of the week and season; and whether different estimates of DEI are obtained when accounting for seasonal variations in spending rates. The results indicate that the relocation increased vendors' profits and satisfaction, the DEI of the new market was much higher than the old, there are daily and seasonal differences in spending rates, and accounting for season resulted in an estimated DEI that was higher than would have been obtained otherwise. Overall, the study demonstrates that location matters – the market's economic outcomes greatly improved by moving from an isolated location on the outskirts of downtown to the city's core.